2018
DOI: 10.4103/jcd.jcd_110_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of grape seed and cranberry extracts in preventing enamel erosion: An optical emission spectrometric analysis

Abstract: Introduction:Dental erosion is defined as the loss of tooth structure due to chemical process that does not involve bacteria. The management of such a condition calls for a comprehensive approach to identifying the cause and treating it.Aim:The aim of this study is to comparatively evaluate the role of grape seed extract (GSE) and cranberry extract (CE) in preventing dental erosion using optical emission spectrometry.Materials and Methods:Prepared enamel specimens were subjected to the erosive challenge using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…The single visit RCT was brought back in the 1950s by 'Ferranti' who advocated the use of diatherapy for pulpal disinfection & H 2 O 2 for irrigation (Manohar and Sharma, 2018;Nasim and Nandakumar, 2018). Oliet et al, in his study, found that there is no difference in the treatment criteria to enhance a successful result between multi-visit & single visit RCT (Mubarak et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The single visit RCT was brought back in the 1950s by 'Ferranti' who advocated the use of diatherapy for pulpal disinfection & H 2 O 2 for irrigation (Manohar and Sharma, 2018;Nasim and Nandakumar, 2018). Oliet et al, in his study, found that there is no difference in the treatment criteria to enhance a successful result between multi-visit & single visit RCT (Mubarak et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Poor oral hygiene can occur at any age -both in youngsters as well as in adults. Systemic diseases that affect the balance between the demineralisation and remineralisation process, however, are more prone to affect the elderly population as opposed to the younger age groups (Nasim and Nandakumar, 2018). Also, a national epidemiological survey showed a 6% -13% reduction in dental caries intensity in children over a ten-year period.…”
Section: Resultsmentioning
confidence: 99%
“…The in-vitro studies conducted at our university includes (Ramanathan and Solete, 2015;Rajendran et al, 2019;Janani et al, 2020), the invivo studies include (Nasim and Nandakumar, 2018;Siddique, 2019), the molecular study (Ramesh et al, 2018;Noor and Others, 2016), the reviews and systematic reviews published are (Kumar and Antony, 2018;Ravinthar and Jayalakshmi, 2018;Rajakeerthi and Ms, 2019), the surveys conducted (Manohar and Sharma, 2018;Jose et al, 2020), and the clinical trial conducted on root canal irrigants were (Teja and Ramesh, 2019;Ramamoorthi et al, 2015). Currently, we are analyzing retrospective studies.…”
Section: Data Collection/tabulationmentioning
confidence: 99%